An updated review of marine macroalgae from continental Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2020)
A bibliographic and herbarium review was carried out to determine the current status of marine macroalgae distributed in the intertidal zone along the profile of continental Ecuador. In this region 4 phyla are recorded: Rhodophyta (92 spp.), Chlorophyta (50 spp.), Ochrophyta (24 spp.) and Charophyta (1 sp.); these comprise a total of 7 classes, 23 orders, 41 families, 62 genera and 167 species distributed throughout the five coastal provinces of Ecuador. Among these, Florideophyceae (Rhodophyta) is the class with the highest number of species on coastal-continental level (90 out of a total of 92 spp.), and the most diverse in each of the analyzed provinces. Charophyta with only one species (Nitella, Characeae) is only recorded in Esmeraldas. At the continental national level, Esmeraldas is the province with the highest number of genera (35) and species (47). The coast of continental Ecuador comprises an insufficiently studied area, the phycological knowledge in this region has increased sixfold in the last 25 years, the generation of taxonomic information continues in increasing order.
Keywords: Continental Ecuador; Macroalgae; Pacific